The Relation Between Free Testosterone and Components of Metabolic Syndrome in Women With Polycystic Ovary Syndrome - Zahra Abbasi Ranjbar; Seyedeh Hajar Sharami; Soudabeh Kazemi; Daniyal Sayyad Abdi; Seyedeh Fatemeh Dalil Heirati (Tehran University of Medical Sciences, 2018)
Objective: To assess the relationship between free testosterone level and components of MS in women with PCOS. Materials and methods: This is a cross-sectional study which was conducted on 215 women with PCOS. PCOS was diagnosed based on the Rotterdam criteria. Patients were divided into two subgroups of patients with and without MS based on ATP III criteria. In each subgroup, the association between individual components of MS with free testosterone was measured. Data were analyzed using SPSS software. Results: The prevalence of MS was 28.8% (n = 62). The mean level of free testosterone in patients with blood pressure ≥ 130/85 was significantly higher than those with blood pressure < 130/85 mm/hg. (p = 0.029) Also, in patients with diastolic blood pressure ≥ 85, the level of free testosterone was significantly higher than patients with diastolic blood pressure < 85. (p = 0.026). Results showed significant positive correlation between the level of free testosterone and cholesterol (p = 0.024). But no significant correlation was noted between levels of free testosterone and other variables. Conclusion: Regarding the relationship between blood pressure and high levels of free testosterone, it seems that regular blood pressure screening has a higher priority of concern comparing other complications for preventing cardiovascular adverse effects in women with PCOS and hyperandrogenism.